2016
DOI: 10.1016/j.sleep.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in sleep characteristics by race/ethnicity in a population-based sample: Chicago Area Sleep Study

Abstract: Background Prior studies report less favorable sleep characteristics among non-Whites as compared with non-Hispanic Whites. However, few population-based studies have used objective measures of sleep duration, especially in more than two racial/ethnic groups. We tested whether objectively-estimated sleep duration and self-reported sleep quality varied by race and whether differences were at least partially accounted for by variability in clinical, psychological and behavioral covariates. Methods Adults aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
105
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(119 citation statements)
references
References 37 publications
11
105
2
1
Order By: Relevance
“…Racial/national differences in sleep quality were examined by using ANOVA followed by the Scheffe post hoc test. Multinomial logistic regression models were used to compute adjusted odds ratios (AORs) and investigate the association between sleep duration and three independent variables (race/nationality, gender, and BMI) with adjustment for potential confounding factors (age, annual family income, days of vigorous-intensity activity, days of moderate-intensity activity, current smoking status, days of alcohol use, having trouble sleeping, sleep disorder, and depression) based on prior research [49][50][51]. Whites were used as the reference group for all multinomial regression models.…”
Section: Discussionmentioning
confidence: 99%
“…Racial/national differences in sleep quality were examined by using ANOVA followed by the Scheffe post hoc test. Multinomial logistic regression models were used to compute adjusted odds ratios (AORs) and investigate the association between sleep duration and three independent variables (race/nationality, gender, and BMI) with adjustment for potential confounding factors (age, annual family income, days of vigorous-intensity activity, days of moderate-intensity activity, current smoking status, days of alcohol use, having trouble sleeping, sleep disorder, and depression) based on prior research [49][50][51]. Whites were used as the reference group for all multinomial regression models.…”
Section: Discussionmentioning
confidence: 99%
“…44 A multilevel framework explicates several mechanisms underlying the disparity, including many CFIR domains such as the outer setting (state/federal regulations, insurance policy), inner setting (cultural sensitivity and diversity of healthcare workforce), and individual providers (biases, skill in working with racial minority populations). 45 There are also several effective clinical interventions for managing asthma in racial minority populations (e.g., patient education, specialty clinics, medications).…”
Section: Incorporating Implementation Science Designs Into Disparitiementioning
confidence: 99%
“…1 A number of epidemiological studies have reported poorer quality sleep and a higher prevalence of short and/or long sleep in non-White adults, particularly from lower socioeconomic status groups, in comparison with White adults. [2][3][4][5] This research has provided crucial information on disparities in such factors as selfreported sleep duration, daytime sleepiness, and symptoms of sleep disordered breathing across ethnic groups, geographical location, and socioeconomic status. However, the underlying racial/ethnic specific factors that may lead to these disparities in sleep health are less well understood.…”
Section: Introductionmentioning
confidence: 99%